Innovations in e-Agricultural Extension Technology (e-AET): diffusion and adoption of agri-expert systems among extension professionals in Kerala - Modem Ravikishore (Department of Agricultural Extension, College of Agriculture, 2014)
The present study entitled 'Innovations in e-Agricultural Extension Technology (e-AET): Diffusion and adoption of agri-expert systems among extension professionals in Kerala' was conducted at Thiruvananthapuram district during 2012-2014 covering 100 extension professionals. Expert systems allows the use and application of information technology and communications technology (lCT's) to access and obtain information related to agricultural production, marketing, distribution, and prices, and the results of agricultural research, innovations, to raise the level of agricultural production and benefit the farming community. The present study, therefore, is with the objective to conduct a systematic appraisal of existing expert systems in agriculture vis a vis their diffusion among the extension professionals. The findings demonstrate that most of the extension professionals either in State Department, NGO or University have positive attitudes towards expert system. Age, training, innovativeness, retrievability, relevancy, format clarity, information content, availability, accuracy and timeliness affect extension professionals' attitudes. Based on respondent's stage in the adopter categorisation with reference to expert systems, it was found that 10 per cent of the sampled respondents belonged to innovators category, 19 per cent respondents belonged to early adopters' category, 32 per cent respondents belonged to early majority category, 24 per cent respondents belonged to late majority category and 15 per cent respondents belonged to laggards' category. Effectiveness index of expert system applications was worked out using seven statements and the results showed that pedagogy (as a means to effective learning through expert system) having highest effectiveness index. The findings demonstrate that most of the respondents belonged to middle age category, holding with master degrees; attended training on lCT. It was also found that most of the respondents having high innovativeness and accessibility, forinat clarity and